MODEL PEMBERDAYAAN MASYARAKAT PESISIR UNTUK MENINGKATKAN EKONOMI, KECAMATAN GALESONG UTARA KABUPATEN TAKALAR SULAWESI SELATAN - Andi Imelda Malik; Kirey Aulia Puteri; Busthan Azikin (Riset Sains dan Teknologi Kelautan, 2023)
North Galesong District, an area located in Takalar Regency, is a coastal area with abundant natural resources and significant economic potential. Coastal areas are areas where sea and land meet. Despite this, people living in the coastal areas of North Galesong sub-district still face economic challenges that need to be addressed. Therefore, it is important to empower coastal communities in North Galesong Sub-district so that they can improve their economy and achieve sustainable development. Empowerment is an effort to increase the capacity and independence of individuals or communities in meeting their own needs. The goal of this paper is to propose a coastal community empowerment model that can be implemented in North Galesong District. The research was conducted by combining a literature review of empowerment models that have been successfully implemented in other coastal areas and analyzing the local situation in North Galesong District. The results show that an empowerment model suitable for North Galesong Sub-district should consider local characteristics and existing economic potential.